2D perovskite microsheets for high-performance photodetectors1. Issue 18 (11th April 2019) - Qian, Liu; Sun, Yilin; Sun, Mengxing; Fang, Zhimin; Li, Lin; Xie, Dan; Li, Chun; Ding, Liming
Abstract : Square-shaped microsheets based on 2D perovskites (PEA)2 SnI4− x Br x ( x = 0, 1, 2) were prepared. A (PEA)2 SnI4 microsheet photodetector gave a photoresponsivity of 3.29 × 10 3 A W −1 with a photoconductive gain of 8.68 × 10 3 . Abstract : Square-shaped microsheets of 2D lead-free perovskite (PEA)2 SnI4− x Br x ( x = 0, 1, 2) were prepared via a ternary-solvent method. The photodetector based on the (PEA)2 SnI4 microsheets gave a photoresponsivity of 3.29 × 10 3 A W −1, a specific detectivity of 2.06 × 10 11 Jones and a photoconductive gain of 8.68 × 10 3 . This is the first time that 2D lead-free perovskite microsheets are used to make high-performance photodetectors.